HUBUNGAN REGULASI EMOSI DENGAN WORK BURNOUT PADA GURU SEKOLAH LUAR BIASA - Vanes, Juwita; Monika , Monika (Provitae: Jurnal Psikologi Pendidikan, 2024)
In carrying out their profession, there are many challenges that special schoolteachers face every day. Special schoolteachers often face complex and challenging situations such as the emotional situations of diverse students and high emotional intensity, so that indirectly special schoolteachers are required to have the ability to manage emotions well to prevent things that can stress teachers. This is called emotional regulation, namely the process of individuals recognizing their emotions, knowing when their emotions appear, and how to show them. Teachers who can control their emotions can create a good and enjoyable learning environment, but teachers with poor emotional regulation skills will lead to undesirable things, one of them is work burnout. Work burnout is an individual response to emotional and interpersonal stressor which keeps happening in workplace. This research aims to find out whether there is a relationship between emotional regulation and work burnout in special schoolteachers. This research uses quantitative research methods and uses gforms to distribute questionnaires to participants. Participants for this research were 233 teachers who worked in Special Schools in the Jakarta area. The measuring instruments used in this research were the Emotion Regulation Questionnaire and the Maslach Burnout Inventory-Educators Survey. The results of the research show that there is a negative and significant relationship between work burnout and emotional regulation in Special School teachers in the Jakarta area.